Development and Implementation of Clinical Practice Guidelines: Current Status in Korea - Ahn, Hyeong Sik (The Korean Academy of Medical Sciences, 2012)
Documentation of unexplained geographic variations in medical practices and use of inappropriate interventions has led to the proliferation of clinical practice guidelines. With increased enthusiasm for guidelines, evidence exists that clinical practice guidelines often influence clinical practices or health outcomes. Their successful implementation may improve the quality of care by decreasing in appropriate variation and expediting the application of effective advances to healthcare practices. In Korea, physicians and healthcare professionals have begun to take interests in clinical practice guidelines. Currently, over 50 practice guidelines have been developed through professional academic organizations or via other routes; however, the quality of the guidelines is unsatisfactory, implementation in clinical settings is incomplete, and there is insufficient infrastructure to develop clinical practice guidelines. Korea must develop policies and invest resources to enhance the development and implementation of clinical practice guidelines.